2013
DOI: 10.1038/nature11877
|View full text |Cite
|
Sign up to set email alerts
|

An outburst from a massive star 40 days before a supernova explosion

Abstract: Various lines of evidence suggest that very massive stars experience extreme mass-loss episodes shortly before they explode as a supernova.[1−4] Interestingly, several models predict such pre-explosion outbursts. [5−7] Establishing a causal connection between these mass-loss episodes and the final supernova explosion will provide a novel way to study pre-supernova massive-star evolution. Here we report on observations of a remarkable mass-loss event detected 40 days prior to the explosion of the Type IIn supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(258 citation statements)
references
References 31 publications
10
246
1
1
Order By: Relevance
“…Motivated by the CJ-SB model for LL GRBs, we consider an extended material with mass M ext ∼ 10 −2 M and radius r ext ∼ 3 × 10 13 cm. WR stars have been observed with such unusually massive envelopes in the months leading up to their SN explosion [77][78][79]. Nakar [31] suggested similar envelope parameters for LL GRB 060218, but without strong constraints on the density profile.…”
Section: B Hydrodynamical Constraints On Choked Jetsmentioning
confidence: 93%
“…Motivated by the CJ-SB model for LL GRBs, we consider an extended material with mass M ext ∼ 10 −2 M and radius r ext ∼ 3 × 10 13 cm. WR stars have been observed with such unusually massive envelopes in the months leading up to their SN explosion [77][78][79]. Nakar [31] suggested similar envelope parameters for LL GRB 060218, but without strong constraints on the density profile.…”
Section: B Hydrodynamical Constraints On Choked Jetsmentioning
confidence: 93%
“…These rise times can also be used to estimate the mass-loss rate of the progenitor system that gave rise to the CSM. Using typical SN Ia-CSM ejecta and wind velocities of a few thousand and 100 km s −1 , respectively, and equations in Ofek et al (2013), we find that SNe Ia-CSM have mass-loss rates of a few times 10 −1 M yr −1 .…”
Section: Ptf12hnrmentioning
confidence: 99%
“…The upper limits on the X-ray luminosity implied by these null detections are ∼10 39 -10 43 erg s −1 ; observed X-ray fluxes of SNe IIn fall in this range (e.g., Pooley et al 2002;Zampieri et al 2005;Immler et al 2007). Using the upper limits determined from the X-ray nondetections of SNe Ia-CSM and equations in Ofek et al (2013), we calculate mass-loss rate upper limits of a few times 10 −1 M yr −1 (which matches the mass-loss rates calculated above using the rise times of SNe Ia-CSM). Prieto et al (2007) found that the host galaxies of the first four discovered SNe Ia-CSM (SNe 1997cy, 1999E, 2002ic, and 2005gj) are all late-type galaxies (dwarf irregulars and late-type spirals) with star formation likely occurring within the last few hundred Myr.…”
Section: Other Observations Of Sne Ia-csmmentioning
confidence: 99%
“…3. In the case of PTF10tel (SN 2010mc), which had a precursor (Ofek et al 2013), we adopt as the SN explosion the mean between the date of the last precursor measurement and the date of the first measurement of the SN (main peak).…”
Section: Appendix Sample Constructionmentioning
confidence: 99%
“…Intense mass loss via eruptive events sometimes manifests itself as precursors prior to the SN explosion , as in SN 2006jc (Pastorello et al 2007), SN 2010mc (Ofek et al 2013), PTF11qcj (Corsi et al 2014), and possibly SN 2009ip (whether an SN was finally produced is controversial; e.g., Mauerhan et al 2013;Graham et al 2014;Margutti et al 2014;Ofek et al 2014;Martin et al 2015). Mass loss from…”
Section: Introductionmentioning
confidence: 99%